Tutu Much Les Ballets Trockadero de Monte Carlo - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Les Ballets Trockadero de Monte Carlo's London return. Peter Anastos's evergreen Go for Barocco is a priceless Balanchine parody. PALABRAS CLAVE: Les Ballets Trockadero de Monte Carlo, Trocks, parody.